Pendidikan Islam Populer: Sebuah Renungan Atas Nasib Pendidikan Madrasah di Tengah Pendidikan Nasional - M. Misbah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: In the course of the history of Islamic education,Islamic schools as institutions of Islamic education was not as expected. One side, in terms of religion, alumni are not able to compete with graduates of boarding schools and on the other hand, in terms of general science, can not compete with public schools. So too, madrasas in education and learning are not in line with communitlr interests, and can not solve the problems faced by society. There has been a